Feasibility study of adaptive radiotherapy for esophageal cancer using artificial intelligence autosegmentation based on MR-Linac - Wang, Huadong; Liu, Xin; Song, Yajun; Yin, Peijun; Zou, Jingmin; Shi, Xihua; Yin, Yong; Li, Zhenjiang (Frontiers in Oncology, 2023)
Purpose. We proposed a scheme for automatic patient-specific segmentation in MR-guided online adaptive radiotherapy based on daily updated, small-sample deep learning models to address the time-consuming delineation of the region of interest (ROI) in the adapt-to-shape (ATS) workflow. Additionally, we verified its feasibility in adaptive radiation therapy for esophageal cancer (EC). Methods and Materials. Nine patients with EC who were treated with an MR-Linac were prospectively enrolled. The actual adapt-to-position (ATP) workflow and simulated ATS workflow were performed, the latter of which was embedded with a deep learning autosegmentation model. The first three treatment fractions of the manual delineations were used as input data to predict the next fraction segmentation, which was modified and then used as training data to update the model daily, forming a cyclic training process. Then, the system was validated in terms of delineation accuracy, time, and dosimetric benefit. Additionally, the esophageal cavity and sternum were added to the ATS workflow (producing ATS+), and the dosimetric variations were assessed. Results. The mean autosegmentation time was 1.40 [1.10-1.78 min]. The Dice similarity coefficient (DSC) of the autosegmentation model gradually approached 1; after four training sessions, the DSCs of all ROIs reached a mean value of 0.9 or more. Furthermore, the planning target volume (PTV) of the ATS plan showed a smaller homogeneity index (HI) than that of the ATP plan. Additionally, V5 and V10 in the lungs and heart were greater in the ATS+ group than in the ATS group. Conclusion. The accuracy and speed of artificial intelligence (AI)-based autosegmentation in the ATS workflow met the clinical radiation therapy needs of EC. This allowed the ATS workflow to achieve a similar speed to the ATP workflow while maintaining its dosimetric advantage. Fast and precise online ATS treatment ensured an adequate dose to the PTV while reducing the dose to the heart and lungs.